Dysregulated Transcript Expression but Not Function of the Glutamate Transporter EAAT2 in the Dorsolateral Prefrontal Cortex in Schizophrenia. - O'Donovan, Sinead M; Shan, Dan; Wu, Xiaojun; Choi, Jae Hyuk; McCullumsmith, Robert E (Schizophrenia Bulletin, 2025)
Background Schizophrenia (SCZ) is a serious mental illness with complex pathology, including abnormalities in the glutamate system. Glutamate is rapidly removed from the synapse by excitatory amino acid transporters (EAATs). Changes in the expression and localization of the primary glutamate transporter EAAT2 are found in the brain in central nervous system (CNS) disorders including SCZ. We hypothesize that neuronal expression and function of EAAT2 are increased in the frontal cortex in subjects diagnosed with SCZ. Study Design EAAT2 protein expression and glutamate transporter function were assayed in synaptosome preparations from the dorsolateral prefrontal cortex (DLPFC) of SCZ subjects and age- and sex-matched nonpsychiatrically ill controls. EAAT2 splice variant transcript expression was assayed in enriched populations of neurons and astrocytes from the DLPFC. Pathway analysis of publicly available transcriptomic datasets was carried out to identify biological changes associated with EAAT2 perturbation in different cell types. Results We found no significant changes in EAAT2 protein expression or glutamate uptake in the DLPFC in SCZ subjects compared with controls (n  = 10/group). Transcript expression of EAAT2 and signaling molecules associated with EAAT2b trafficking (CaMKIIa and DLG1) were significantly altered in enriched populations of astrocytes and pyramidal neurons (P  < .05) in SCZ (n  = 16/group). These changes were not associated with antipsychotic medications. Pathway analysis also identified cell-type-specific enrichment of biological pathways associated with perturbation of astrocyte (immune pathways) and neuronal (metabolic pathways) EAAT2 expression. Conclusions Overall, these data support the growing body of evidence for the role of dysregulation of the glutamate system in the pathophysiology of SCZ.